Evaluation of medication adherence and medication beliefs among patients with epilepsy - Dayapoglu, Nuray; Turan, Gulcan Bahcecioglu; Ozer, Zulfunaz (Academic Press Inc Elsevier Science, 2021)
Aim: This study explored medication adherence and medication beliefs of patients with epilepsy and evaluated the relationship between these two factors. Methods: This descriptive, cross-sectional, correlational study was conducted with 174 patients with epilepsy who were referred to the neurology outpatient clinic of a university hospital in Erzurum, Turkey, between February 10, 2020 and December 30, 2020. The data were collected using the Descriptive Information Form, The eight-item Morisky Medication Adherence Scale (MMAS-8), and the Beliefs about Medicines Questionnaire (BMQ-T). Results: The mean age of the patients was 33.06 +/- 11.94 years, and the mean duration of time since diagnosis was 12.91 +/- 10.73 years. In terms of demographic information, 60.3% of the patients were single, 58% had low income or were unemployed, 53.4% had five or more seizures within the last year, 40.8% had focal onset seizures, 69% had no other chronic disease, and 76.4% used more than one medicine. The patients' mean MMAS-8 score was 3.25 +/- 2.13. The mean scores for the specific concern subscale was 3.65 +/- 0.85, 1.81 +/- 0.75 for the specific necessity subscale, 4.19 +/- 0.76 for the general overuse sub scale, and 3.14 +/- 1.41 for the general harm subscale. The regression analysis revealed that general overuse and general harm negatively affected the MMAS-8 total score. Conclusion: Patients with epilepsy reported low medication adherence and were found to have concerns about the harms and side effects of the medicines they were using; they had negative perceptions of the purpose of medicines; they had high beliefs about the harms of medicines; and they had low beliefs about their personal treatment needs. The patients were generally found to have negative beliefs about medicines, which negatively affected their medication adherence. (c) 2021 Elsevier Inc. All rights reserved.
Keywords: Epilepsy; Patient; Medication adherence